Productivity analysis and improvement of the production department at PT. Pojur - Madura using the objective matrix (OMAX) method - Emon Rifa'i,; Rachmad Hidayat,; Ummi Badiyatus Shalihah, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The growth of the industrial sector in 2023 will increase, this condition is reflected in the trend of the level of expansion in the value of the Industrial Confidence Index (IKI) which has increased. PT. Pojur is a company located in the Sumenep area engaged in the gas cylinder industry. For a business to survive and continue to grow, a business must be able to compete by maintaining product quality. One of the company's strategies that can be used is by measuring the company's productivity. This is used to determine the extent to which the effectiveness of the products produced and the efficiency of the use of resources owned by PT. Pojur. Several variables that affect productivity include raw materials, energy and labor used. The purpose of this study is to find out what the productivity index is at PT. Pojur with the Objective matrix (OMAX) method. The results of measuring productivity during the period January to December 2022 show a productivity of 19%, while the highest productivity occurs in November and December with a total of 26% and the lowest productivity is in January with a total of 0% and the cause of decreased productivity in the production section is lack of maintenance on machines and the lack of operator expertise in carrying out production.